Precision feeding in gestating sows: a retrospective analysis of lysine intake and pregnancy outcomes - P. Langendijk; A.K. Agyekum; F. Simard; M. Richer-Lanciault (Livestock Science, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

The effects of ectomycorrhizal fungal networks on seedling establishment are contingent on species and severity of overstorey mortality - Gregory J. Pec; Suzanne W. Simard; James F. Cahill; Justine Karst (Mycorrhiza, 2020)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Temporal and spatial mapping of red grouper Epinephelus morio sound production - C. C. Wall; P. Simard; M. Lindemuth; C. Lembke; D. F. Naar; C. Hu; B. B. Barnes; F. E. Muller‐Karger; D. A. Mann (Journal of Fish Biology, 2014)
The goals of this project were to determine the daily, seasonal and spatial patterns of red grouper Epinephelus morio sound production on the West Florida Shelf ( WFS ) using passive acoustics. An 11 month time series of acoustic data from fixed recorders deployed at a known E. morio aggregation site showed that E. morio produce sounds throughout the day and during all months of the year. Increased calling (number of files containing E. morio sound) was correlated to sunrise and sunset, and peaked in late summer (July and August) and early winter (November and December). Due to the ubiquitous production of sound, large‐scale spatial mapping across the WFS of E. morio sound production was feasible using recordings from shorter duration‐fixed location recorders and autonomous underwater vehicles ( AUVs ). Epinephelus morio were primarily recorded in waters 15–93 m deep, with increased sound production detected in hard bottom areas and within the Steamboat Lumps Marine Protected Area (Steamboat Lumps). AUV tracks through Steamboat Lumps, an offshore marine reserve where E. morio hole excavations have been previously mapped, showed that hydrophone‐integrated AUVs could accurately map the location of soniferous fish over spatial scales of

Decline of ectomycorrhizal fungi following a mountain pine beetle epidemic - Roland Treu; Justine Karst; Morgan Randall; Gregory J. Pec; Paul W. Cigan; Suzanne W. Simard; Janice E. K. Cooke; Nadir Erbilgin; James F. Cahill (Ecology, 2014)
Forest die‐off caused by mountain pine beetle (MPB; Dendroctonus ponderosa ) is rapidly transforming western North American landscapes. The rapid and widespread death of lodgepole pine ( Pinus contorta ) will likely have cascading effects on biodiversity. One group particularly prone to such declines associated with MPB are ectomycorrhizal fungi, symbiotic organisms that can depend on pine for their survival, and are critical for stand regeneration. We evaluated the indirect effects of MPB on above‐ (community composition of epigeous sporocarps) and belowground (hyphal abundance) occurrences of ectomycorrhizal fungi across 11 forest stands. Along a gradient of mortality (0–82% pine killed), macromycete community composition changed; this shift was driven by a decrease in the species richness of ectomycorrhizal fungi. Both the proportion of species that were ectomycorrhizal and hyphal length in the soil declined with increased MPB‐caused pine mortality; 70% in stands without MPB attacks. The rapid range expansion of a native insect results not only in the widespread mortality of an ecologically and economically important pine species, but the effect of MPB may also be exacerbated by the concomitant decline of fungi crucial for recovery of these forests.

Effects of observed and experimental climate change on terrestrial ecosystems in northern Canada: results from the Canadian IPY program - Gregory H. R. Henry; Karen A. Harper; Wenjun Chen; Julie R. Deslippe; Robert F. Grant; Peter M. Lafleur; Esther Lévesque; Steven D. Siciliano; Suzanne W. Simard (Climatic Change, 2012)

What explains landscape patterns of tree mortality caused by bark beetle outbreaks in Greater Yellowstone? - Martin Simard; Erinn N. Powell; Kenneth F. Raffa; Monica G. Turner (Global Ecology and Biogeography, 2012)
Aim Bark beetle outbreaks have recently affected extensive areas of western North American forests, and factors explaining landscape patterns of tree mortality are poorly understood. The objective of this study was to determine the relative importance of stand structure, topography, soil characteristics, landscape context (the characteristics of the landscape surrounding the focal stand) and beetle pressure (the abundance of local beetle population eruptions around the focal stand a few years before the outbreak) to explain landscape patterns of tree mortality during outbreaks of three species: the mountain pine beetle, which attacks lodgepole pine and whitebark pine; the spruce beetle, which feeds on Engelmann spruce; and the Douglas‐fir beetle, which attacks Douglas‐fir. A second objective was to identify common variables that explain tree mortality among beetle–tree host pairings during outbreaks. Location Greater Yellowstone ecosystem, Wyoming, USA. Methods We used field surveys to quantify stand structure, soil characteristics and topography at the plot level in susceptible stands of each forest type showing different severities of infestation (0–98% mortality; n = 129 plots). We then used forest cover and beetle infestation maps derived from remote sensing to develop landscape context and beetle pressure metrics at different spatial scales. Plot‐level and landscape‐level variables were used to explain outbreak severity. Results Engelmann spruce and Douglas‐fir mortality were best predicted using landscape‐level variables alone. Lodgepole pine mortality was best predicted by both landscape‐level and plot‐level variables. Whitebark pine mortality was best – although poorly – predicted by plot‐level variables. Models including landscape context and beetle pressure were much better at predicting outbreak severity than models that only included plot‐level measures, except for whitebark pine. Main conclusions Landscape‐level variables, particularly beetle pressure, were the most consistent predictors of subsequent outbreak severity within susceptible stands of all four host species. These results may help forest managers identify vulnerable locations during ongoing outbreaks.

Inflammation of the Choroid Plexus and Ependymal Layer of the Ventricle Following Intraventricular Hemorrhage - Philippe F. Simard; Cigdem Tosun; Ludmila Melnichenko; Svetlana Ivanova; Volodymyr Gerzanich; J. Marc Simard (Translational Stroke Research, 2011)

Insertion polymorphism of transposable elements and population structure of Anopheles gambiae M and S molecular forms in Cameroon - M. BOULESTEIX; F. SIMARD; C. ANTONIO‐NKONDJIO; H. P. AWONO‐AMBENE; D. FONTENILLE; C. BIÉMONT (Molecular Ecology, 2007)
The insertion polymorphism of five transposable element (TE) families was studied by Southern blots in several populations of the M and S molecular forms of the mosquito Anopheles gambiae sensu stricto from southern Cameroon. We showed that the mean TE insertion site number and the within‐population insertion site polymorphism globally differed between the M and S molecular forms. The comparison of the TE insertion profiles of the populations revealed a significant differentiation between these two molecular forms (0.163 ST

Phosphorus Transformations under Reduction in Long-term Manured Soils - F. Ajmone-Marsan; D. Côté; R. R. Simard (Plant and Soil, 2006)

Impact of insecticide‐treated bed nets implementation on the genetic structure of Anopheles arabiensis in an area of irrigated rice fields in the Sahelian region of Cameroon - C. WONDJI; F. SIMARD; T. LEHMANN; E. FONDJO; A. SAMÈ‐EKOBO; D. FONTENILLE (Molecular Ecology, 2005)
Variation at 12 microsatellite loci was investigated to assess the impact of the implementation of insecticide‐treated bed nets (ITNs) on the genetic structure of Anopheles arabiensis in Simatou, a village surrounded by irrigated rice fields in the Sahelian area of Cameroon. The An. arabiensis population of Simatou was sampled twice before ITN implementation, and twice after. Effective population size estimates ( N e ) were similar across each time point, except for the period closely following ITN introduction where a nonsignificant reduction was recorded. Hence, we believe that ITN implementation resulted in a temporary bottleneck, rapidly followed by a demographic expansion. The genetic diversity of the population was not significantly affected since different genetic parameters (allele number, observed and expected heterozygosities) remained stable. Low estimates of genetic differentiation between the populations from Simatou and Lagdo, separated by 300 km, suggested extensive gene flow among populations of An. arabiensis in the Sahelian region of Cameroon. A decrease in the susceptibility to deltamethrin was observed following ITN introduction, but no kdr mutation was detected and a metabolic resistance mechanism is probably involved. The temporary effect of ITNs on the genetic structure of An. arabiensis population suggests that, to optimize the success of any control programme of this species based on ITNs, the control area should be very large and the programme should be implemented for a long period of time.

PCNA Up-Regulation in Cerebral Vessels with Angiotensin II-Hypertension: Abnormal Regulation of Ca2+ Channel and Nitrate Tolerance Associated with Alternative Splicing of cGKI - A. Ivanov; S. Ivanova; L. V. Melnitchenko; V. Gerzanich; M. F. Shuba; J. M. Simard (Neurophysiology, 2003)

Mapping of the bovine herpesvirus 1 glycoprotein C promoter region and its specific transactivation by the viral BICP27 gene product - F. Hamel; C. Simard (Archives of Virology, 2003)

Genetic Determinants of Pseudomonas aeruginosa Colonization in Cystic Fibrosis Patients in Canada - M. De Braekeleer; C. Allard; J.-P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Genetic determinants ofPseudomonas aeruginosa colonization in cystic fibrosis patients in Canada - M. Braekeleer; C. Allard; J. -P. Leblanc; G. Aubin; F. Simard (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Synthetic peptides corresponding to the F protein of RSV stimulate murine B and T cells but fail to confer protection - M. Trudel; E. J. Stott; G. Taylor; D. Oth; G. Mercier; F. Nadon; C. Séguin; C. Simard; M. Lacroix (Archives of Virology, 1991)

Comparison of caprine, human and bovine strains of respiratory syncytial virus - M. Trudel; F. Nadon; C. Simard; F. Bélanger; R. Alain; C. Séguin; G. Lussier (Archives of Virology, 1989)